Correlation between Methicillin-Resistant Staphylococcus aureus Infection with Length of Stay and Mortality at Gunung Jati Regional Hospital, Cirebon, Indonesia: A Case Control Study with Total Sampling - Azmi, Ranidaa' Diyaa'; Indrakusuma, Mohammad Erwin; Dewangga, Taufan Herwindo (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: In 2017, WHO identified Methicillin-Resistant Staphylococcus aureus (MRSA) as a high-priority pathogen due to its antimicrobial resistance. MRSA prevalence has been rising since the 1960s, reaching 20% globally and over 80% in some countries. This increasing prevalence of MRSA is accompanied by higher morbidity, more challenging management with difficult treatment, and prolonged length of stay, and consequently increased mortality risk. Aims: To determine the relationship between MRSA infection with length of stay and mortality at Gunung Jati Regional Hospital, Cirebon, Indonesia. Methods: A case-control study was performed in 46 cases and 92 controls. This study used total sampling including 138 samples, selected population of MRSA patients between 2021-2023 at Gunung Jati Regional Hospital, Cirebon. Data was taken from medical record and WHONET data. Results: The Mann-Whitney test results showed a significant correlation between MRSA infection and the length of stay compared to MSSA infection (p=0.003). Furthermore, the Chi-Square test revealed a significant correlation between MRSA infection and mortality (p=0.019; OR, 2.448; 95% CI, 1.151 – 5.205). Conclusion: Methicillin-Resistant Staphylococcus aureus infection is associated with a longer length of stay and higher mortality compared to Methicillin-Sensitive Staphylococcus aureus infection. Received: 25 September 2024 | Reviewed: 21 October 2024 | Revised: 30 November 2024 | Accepted: 15 December 2024.